Liquid‐Metal‐Based Dynamic Thermoregulating and Self‐Powered Electronic Skin. (18th April 2021) - Xiang, Shengxin; Liu, Dongjuan; Jiang, Chenchao; Zhou, Wenmin; Ling, Dan; Zheng, Wentao; Sun, Xiupeng; Li, Xing; Mao, Yanchao; Shan, Chongxin
Abstract: Electronic skin (E‐skin) is an emerging and promising human‐machine interface. Besides skin‐like functions of tactile perception and stretchability, skin‐like comfortabilities, including breathability, moisture permeability, softness, and thermoregulating ability are, also crucial factors for E‐skins. Thermoregulation is one of the most important roles of human skin. People can feel comfortable when their skins are regulated at a certain range of temperature. Moreover, it is a dynamic process according to the surrounding temperature. Current E‐skins do not have the function of dynamically regulating their temperature. Here, a thermoregulating E‐skin (TE‐skin) based on liquid metal as a phase change material with its melting point in the comfortable temperature range of human skin is reported. Compared with conventional E‐skins, the TE‐skin can dynamically termoregulate according to the surrounding temperature through a phase change. Combining with the principle of triboelectric nanogenerator, the TE‐skin is also able to act as a self‐powered sensor. Based on the self‐powered TE‐skin, an intelligent dialing communications system is further developed, which can be used to call a cellphone on human skin. For the first time, this study introduces the dynamic thermoregulating concept to E‐skins and could open up new opportunities for E‐skin developments. Abstract : A dynamic thermoregulating electronic skin (TE‐skin) is developed based on the liquid metal as a phase change material. An intelligent dialing communications system is further developed, which could call a cellphone on the human skin by using the self‐powered TE‐skin. With abilities of thermoregulation, electricity generation, and intelligent control, this TE‐skin could open up new opportunities for E‐skin developments.